Endless belt for electrophotographic apparatus
By using modified polyamide imide resin in the base layer of the annular belt for electrophotography equipment and adding specific additives, the problems of insufficient mold release properties and poor friction coefficient are solved, and a more efficient mold release process and better physical properties are achieved.
Patent Information
- Application Number
- CN202411162409.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-08-31
- Filing Date
- 2024-08-23
- Publication Date
- 2025-02-28
AI Technical Summary
The friction coefficient of the annular belt for existing electrophotographic equipment is poor during the demolding process, resulting in insufficient demolding properties, increasing production costs and affecting physical properties.
Modified polyamide imide resin is used as the base material, and the aromatic isocyanate compounds, aromatic polycarboxylic acid anhydrides and silicone polymers are copolymerized, and polyalkylene imine and polyoxyethylene alkyl ether are added to the base layer to improve the mold release property and maintain the friction coefficient.
It is achieved to improve the release property and friction coefficient of the annular belt without increasing the cost, and to enhance the durability and elongation of the annular belt.
Smart Images

Figure CN119529529A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to an endless belt for an electrophotographic device, and more particularly, to an endless belt for an electrophotographic device, which is used as a conveyor belt, an intermediate transfer belt, etc. in an electrophotographic device such as a full-color LBP (laser beam printer) and a full-color MFP (multi-function printer) that adopts electrophotographic technology. Background Art
[0002] As endless belts such as conveyor belts and intermediate transfer belts of electrophotographic equipment, there are known endless belts having a base layer made of fluorine-based resin or polyamide resin mixed with conductive carbon black. In addition, there are also known endless belts having a base layer made of polyamideimide resin.
[0003] Prior art literature Patent Literature Patent Document 1: Japanese Patent Application Publication No. 2005-281670. Summary of the invention
[0004] Problems to be solved by the invention The base layer of the endless belt can be produced, for example, by coating a base layer forming material on a cylindrical mold and then demolding the mold. At this time, in order to easily extract the base layer of the endless belt from the mold, a release agent is applied to the mold surface, or a release agent is added to the base layer forming material. The method of applying a release agent to the mold surface is disadvantageous in terms of cost due to the management process of the coating, etc. The method of adding a release agent to the base material is particularly important because it affects the physical properties of the base material.
[0005] The problem to be solved by the present invention is to provide an endless belt for an electrophotographic apparatus which maintains the friction coefficient and improves the mold release property.
[0006] Means used to solve problems In order to solve the above problems, the endless belt for an electrophotographic device according to the present invention is driven in the circumferential direction in a state where the surface is in contact with or close to a photoreceptor, wherein the base layer is formed using a modified polyamide-imide resin obtained by copolymerizing the following (A) to (C), and contains polyalkylene imine and polyoxyethylene alkyl ether. (A) aromatic isocyanate compounds, (B) anhydrides of aromatic polycarboxylic acids, (C) An organic silicon polymer having a polydimethylsiloxane structure in a molecule and having a reactive group with respect to the isocyanate group of (A) at one or both ends.
[0007] Relative to 100 parts by mass of the modified polyamide-imide resin, the polyalkylene imine is preferably 0.2 parts by mass or more and 20 parts by mass or less, and the polyoxyethylene alkyl ether is preferably 0.1 parts by mass or more and 5 parts by mass or less. The organosilicon polymer (C) preferably has a reactive group of at least one of two hydroxyl groups and a carboxyl group at a single end. The mixing ratio of the organosilicon polymer (C) is preferably 1% by mass or more and 20% by mass or less of the total amount of (A) to (C). The number of carbon atoms of the alkylene group of the polyalkylene imine is preferably 2 or more and 4 or less. The number of carbon atoms of the alkyl group of the polyoxyethylene alkyl ether is preferably 8 or more and 16 or less.
[0008] (1) The endless belt for an electrophotographic device according to the present invention is driven in the circumferential direction with its surface in contact with or close to a photoreceptor, wherein the base layer is formed using a modified polyamide-imide resin obtained by copolymerizing the following (A) to (C), and contains a polyalkyleneimine and a polyoxyethylene alkyl ether. (A) aromatic isocyanate compounds, (B) anhydrides of aromatic polycarboxylic acids, (C) An organic silicon polymer having a polydimethylsiloxane structure in a molecule and having a reactive group with respect to the isocyanate group of (A) at one or both ends.
[0009] (2) In the above (1), the polyalkylene imine is preferably in an amount of 0.2 to 20 parts by mass, and the polyoxyethylene alkyl ether is preferably in an amount of 0.1 to 5 parts by mass, based on 100 parts by mass of the modified polyamide-imide resin.
[0010] (3) In the above (1) or (2), the organosilicon polymer (C) preferably has a total of two reactive groups of at least one of a hydroxyl group and a carboxyl group at one terminal.
[0011] (4) In any one of the above (1) to (3), the blending ratio of the silicone polymer (C) is preferably 1 mass % or more and 20 mass % or less of the total amount of the (A) to (C).
[0012] (5) In any one of the above (1) to (4), the alkylene group of the polyalkylene imine preferably has 2 or more and 4 or less carbon atoms.
[0013] (6) In any one of the above (1) to (5), the alkyl group of the polyoxyethylene alkyl ether preferably has 8 or more and 16 or less carbon atoms.
[0014] Effects of the Invention According to the endless belt for electrophotographic equipment of the present invention, the base layer is formed using a modified polyamide-imide resin obtained by copolymerizing the above-mentioned (A) to (C) and contains polyalkyleneimine and polyoxyethylene alkyl ether, so that the friction coefficient can be maintained and the mold release property can be improved.
[0015] When the polyalkylene imine is 0.2 to 20 parts by mass and the polyoxyethylene alkyl ether is 0.1 to 5 parts by mass relative to 100 parts by mass of the modified polyamide-imide resin, both the effect of maintaining the friction coefficient and the effect of improving the releasability can be highly simultaneously achieved.
[0016] Furthermore, when the organosilicon polymer (C) has at least one reactive group of a hydroxyl group and a carboxyl group at a single terminal, the reactive group (hydroxyl group or carboxyl group) at a single terminal of the organosilicon polymer directly reacts with the isocyanate group of the aromatic isocyanate compound, and the polydimethylsiloxane structure can be incorporated into the polyamide-imide resin in the form of a graft copolymer. Therefore, during the heat treatment, the polydimethylsiloxane structure is deviated from the surface side of the base layer, and the friction coefficient can be particularly reduced.
[0017] Furthermore, when the blending ratio of the silicone polymer (C) is 1% by mass or more and 20% by mass or less of the total amount of (A) to (C), the durability and elongation are excellent.
[0018] Furthermore, when the carbon number of the alkylene group of the polyalkylene imine is 2 or more and 4 or less, the effect of improving the mold releasability is excellent.
[0019] Furthermore, when the carbon number of the alkyl group of the polyoxyethylene alkyl ether is 8 or more and 16 or less, the effect of improving the mold releasability is excellent. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 This is a perspective view schematically showing an endless belt for an electrophotographic device according to one embodiment of the present invention.
[0021] Figure 2 yes Figure 1 A cross-sectional view of an endless belt for an electrophotographic apparatus is shown.
[0022] Description of Reference Numerals 10: Annular belt; 12: Grassroots; 14: Surface. DETAILED DESCRIPTION
[0023] The endless belt for an electrophotographic apparatus (hereinafter, sometimes simply referred to as an endless belt) according to the present invention will be described in detail.
[0024] exist Figure 1 An endless belt according to one embodiment of the present invention is shown in FIG. Figure 2 Shown in Figure 1 A cross-sectional view of the annular belt is shown.
[0025] The endless belt 10 includes a cylindrical base layer 12 and a surface layer 14 formed on the outer peripheral surface of the base layer 12 .
[0026] The base layer 12 serves as a base material of the endless belt 10. The base layer 12 is formed in a cylindrical shape and has a seamless structure without any seams in the circumferential direction.
[0027] The base layer 12 is formed of a modified polyamide-imide resin obtained by copolymerizing the following (A) to (C), and contains polyalkylene imine and polyoxyethylene alkyl ether. (A) aromatic isocyanate compounds, (B) anhydrides of aromatic polycarboxylic acids, (C) An organic silicon polymer having a polydimethylsiloxane structure in a molecule and having a reactive group with respect to the isocyanate group of (A) at one or both ends.
[0028] The aromatic isocyanate compound (A) is not particularly limited as long as it is an isocyanate compound having an aromatic ring in the molecule. As the aromatic isocyanate compound (A), diphenylmethane diisocyanate (MDI), toluene diisocyanate (TDI), dimethyl diphenyl diisocyanate (TODI), xylylene diisocyanate (XDI), lysine diisocyanate (LDI), naphthalene diisocyanate (NDI), p-phenylene diisocyanate (PPDI), tetramethyl xylylene diisocyanate (TMXDI), etc. can be listed. Regarding the aromatic isocyanate compound (A), one of them can be used alone, or two or more can be used in combination. Among them, MDI and TODI are preferred in terms of reactivity, cost, and solubility.
[0029] The anhydride (B) of the aromatic polycarboxylic acid is not particularly limited as long as it has an aromatic ring in the molecule and undergoes a condensation reaction with the aromatic isocyanate compound (A). Examples of the anhydride (B) of the aromatic polycarboxylic acid include aromatic polycarboxylic acid anhydride (B1), aromatic polycarboxylic acid dianhydride (B2), and the like.
[0030] Examples of the aromatic polycarboxylic acid anhydride (B1) include trimellitic anhydride (trimellitic anhydride), naphthalene-1,2,4-tricarboxylic anhydride, etc. Among them, trimellitic anhydride (trimellitic anhydride) is preferred from the viewpoints of reactivity, cost, and solubility.
[0031] Examples of the aromatic polycarboxylic acid dianhydride (B2) include benzene-1,2,4,5-tetracarboxylic dianhydride (pyromellitic dianhydride), benzophenone-3,3',4,4'-tetracarboxylic dianhydride, diphenyl ether-3,3',4,4'-tetracarboxylic dianhydride, benzene-1,2,3,4-tetracarboxylic dianhydride, biphenyl-3,3',4,4'-tetracarboxylic dianhydride, biphenyl-2,2',3,3'-tetracarboxylic dianhydride, naphthalene-2,3,6,7-tetracarboxylic dianhydride, naphthalene-1,2,4,5-tetracarboxylic dianhydride, naphthalene-1,4,5,8-tetracarboxylic dianhydride, decahydronaphthalene-1,4,5,8-tetracarboxylic dianhydride, 4,8-dimethyl-1,2,3,5,6,7-hexahydronaphthalene-1,2,5,6-tetracarboxylic dianhydride, and 2,6-dichloronaphthalene-1,4,5,8-tetracarboxylic dianhydride. Dianhydride, 2,7-dichloronaphthalene-1,4,5,8-tetracarboxylic dianhydride, 2,3,6,7-tetrachloronaphthalene-1,4,5,8-tetracarboxylic dianhydride, phenanthrene-1,3,9,10-tetracarboxylic dianhydride, perylene-3,4,9,10-tetracarboxylic dianhydride, bis(2,3-dicarboxyphenyl)methane dianhydride, bis(3,4-dicarboxyphenyl)methane dianhydride, 1,1-bis(2,3-dicarboxyphenyl)methane dianhydride The present invention also includes bis(3,4-dicarboxyphenyl)ethane dianhydride, 1,1-bis(3,4-dicarboxyphenyl)ethane dianhydride, 2,2-bis(2,3-dicarboxyphenyl)propane dianhydride, 2,3-bis(3,4-dicarboxyphenyl)propane dianhydride, bis(3,4-dicarboxyphenyl)sulfone dianhydride, bis(3,4-dicarboxyphenyl)ether dianhydride, ethylene glycol bis(anhydrotrimellitate), propylene glycol bis(anhydrotrimellitate), etc. Among them, ethylene glycol bis(anhydrotrimellitate) is preferred from the viewpoints of reactivity, cost, and solubility.
[0032] The anhydride (B) of an aromatic polycarboxylic acid may be used alone or in combination of two or more thereof. In addition, an aromatic polycarboxylic acid may be used together with the anhydride (B) of an aromatic polycarboxylic acid. The anhydride (B) of an aromatic polycarboxylic acid is preferably used in combination with B1 and B2. If B1 and B2 are used in combination, the ratio of the imide group in the modified polyamide-imide resin increases, so that the water absorption decreases, and the bending tendency of the endless belt 10 can be improved.
[0033] When B1 and B2 are used together, the molar mixing ratio of B1 to B2 is preferably in the range of B1 / B2 = 90 / 10 to 50 / 50. More preferably, it is in the range of B1 / B2 = 80 / 20 to 60 / 40. If the molar mixing ratio of B1 to B2 is within the above range, the deterioration of the bending resistance can be suppressed, and the bending tendency of the endless belt 10 can be improved.
[0034] The silicone polymer (C) has a polydimethylsiloxane structure in the molecule and has a reactive group to the isocyanate group of (A) at one end or both ends. The reactive group of the silicone polymer (C) reacts directly with the isocyanate group of the aromatic isocyanate compound (A), and the polydimethylsiloxane structure is incorporated into the polyamide-imide resin in the form of a block copolymer or a graft copolymer. As a result, the bending resistance of the polyamide-imide resin with high rigidity can be improved. In addition, since the polydimethylsiloxane structure is incorporated into the polyamide-imide resin, the friction coefficient can be reduced.
[0035] As the organosilicon polymer (C), there can be listed an organosilicon polymer having one reactive group at each of the two ends and an organosilicon polymer having two reactive groups at one end. As the reactive group, there can be listed a hydroxyl group, a carboxyl group, and an amino group. As the organosilicon polymer having one reactive group at each of the two ends, there can be listed a carboxylic acid two-terminal organosilicon polymer having one carboxyl group at each of the two ends (for example, "BY16-750" manufactured by Toray DowCorning Silicone, etc.). As the organosilicon polymer having two reactive groups at one end, there can be listed a single-terminal bifunctional organosilicon polymer having two hydroxyl groups at one end (for example, "X-22-176DX" manufactured by Shin-Etsu Chemical Co., Ltd., etc.).
[0036] When the organosilicon polymer (C) is an organosilicon polymer having hydroxyl groups or carboxyl groups at both ends, the reactive groups (hydroxyl groups or carboxyl groups) at both ends of the organosilicon polymer (C) react directly with the isocyanate groups of the aromatic isocyanate compound (A), and a polydimethylsiloxane structure can be incorporated into the polyamide-imide resin in the form of a chimeric copolymer. This improves the bending resistance.
[0037] When the organosilicon polymer (C) is an organosilicon polymer having at least one of two reactive groups of a hydroxyl group and a carboxyl group at one end, the reactive group (hydroxyl group or carboxyl group) at one end of the organosilicon polymer (C) directly reacts with the isocyanate group of the aromatic isocyanate compound (A), and a polydimethylsiloxane structure can be incorporated into the polyamide-imide resin in the form of a graft copolymer. In this way, during heat treatment, the polydimethylsiloxane structure is biased toward the surface side of the base layer 12, and the friction coefficient can be particularly reduced.
[0038] The hydroxyl value or acid value of the silicone polymer (C) is preferably in the range of 1 to 1000 mgKOH / g. More preferably, it is in the range of 4 to 150 mgKOH / g. The number average molecular weight (Mn) of the silicone polymer (C) is preferably in the range of 200 to 40,000. More preferably, it is in the range of 1,000 to 20,000.
[0039] The proportion of the organosilicon polymer (C) is preferably 1% by mass or more and 20% by mass or less of the total amount of the above-mentioned (A) to (C). More preferably, it is 2% by mass or more and 15% by mass or less. When the proportion of the organosilicon polymer (C) is 1% by mass or more, the durability of the endless belt 10 is excellent. In addition, when the proportion of the organosilicon polymer (C) is 20% by mass or less, the elongation of the endless belt 10 can be ensured.
[0040] The modified polyamide-imide resin may be a modified polyamide-imide resin obtained by copolymerizing the above (A) to (C), or a modified polyamide-imide resin obtained by copolymerizing a carboxylic acid terminal polymer (D) together with the above (A) to (C). Since the carboxylic acid terminal polymer (D) functions as a soft segment, the modified polyamide-imide resin is given flexibility, the elongation at break of the endless belt 10 is increased, and the durability is improved.
[0041] The polymer (D) having carboxylic acid at both ends is not particularly limited as long as it has one carboxylic acid at each end of the polymer. Examples of the polymer (D) having carboxylic acid at both ends include polybutadiene having carboxylic acid at both ends, hydrogenated polybutadiene having carboxylic acid at both ends, polyester having carboxylic acid at both ends, polyamide having carboxylic acid at both ends, and polyacrylonitrile-butadiene copolymer having carboxylic acid at both ends. In the modified polyamide-imide resin, the polymer (D) having carboxylic acid at both ends may include only one of them, or may include two or more thereof.
[0042] The polymer (D) having carboxylic acid at both ends is obtained by introducing carboxylic acid at both ends of the polymer using a known method. Examples of the introduced carboxylic acid include aliphatic carboxylic acids and aromatic carboxylic acids. Examples of aliphatic carboxylic acids include adipic acid, sebacic acid, suberic acid, oxalic acid, succinic acid, suberic acid, azelaic acid, dodecanedioic acid, undecanedioic acid, maleic acid, fumaric acid, itaconic acid, and the like. Examples of aromatic carboxylic acids include terephthalic acid, isophthalic acid, phthalic acid, chlorophthalic acid, and nitrophthalic acid.
[0043] The acid value of the polymer (D) having carboxylic acid at both ends is preferably in the range of 15 to 150 mgKOH / g. More preferably, it is in the range of 45 to 110 mgKOH / g. The number average molecular weight (Mn) of the polymer (D) having carboxylic acid at both ends is preferably in the range of 750 to 7500. More preferably, it is in the range of 1000 to 2500.
[0044] The proportion of the polymer (D) containing carboxylic acid at both ends is preferably in the range of 5 to 50% by mass of the total amount of the above-mentioned (A) to (D). More preferably, it is in the range of 10 to 30% by mass. If the proportion of the polymer (D) containing carboxylic acid at both ends is 5% by mass or more, durability can be ensured. If the proportion of the polymer (D) containing carboxylic acid at both ends is 50% by mass or less, it is easy to suppress the deterioration of the creep rate.
[0045] The molar mixing ratio of the total molar number (a) of the isocyanate group of the aromatic isocyanate compound (A), the total molar number (b) of the anhydride group and the carboxyl group of the aromatic polycarboxylic acid anhydride (B), and the total molar number (d) of the carboxyl group of the carboxylic acid terminal polymer (D) [(b) + (d)] is preferably in the range of (a) / [(b) + (d)] = 90 / 100 to 130 / 100. More preferably, it is in the range of (a) / [(b) + (d)] = 100 / 100 to 120 / 100. If the value of (a) / [(b) + (d)] is in the preferred range, the molecular weight of the modified polyamide-imide resin can be increased, and durability can be ensured.
[0046] The modified polyamide-imide resin can be prepared as follows. Prepare a reaction container equipped with a stirrer, a nitrogen inlet pipe, a thermometer, and a cooling pipe, add a predetermined amount of an aromatic isocyanate compound (A), an anhydride of an aromatic polycarboxylic acid (B), and an organosilicon polymer (C), and if necessary, add a predetermined amount of a carboxylic acid terminal polymer (D), add N-methyl-2-pyrrolidone (NMP), N,N-dimethylformamide (DMF), N,N-dimethylacetamide (DMAC), γ-butyrolactone and other polar solvents, and heat to a predetermined temperature (preferably 130-150°C) for a predetermined time (preferably 1-3 hours) under a nitrogen flow while stirring. Then, the reaction is stopped after reacting at a predetermined temperature (preferably 130-150°C) for a predetermined time (preferably about 3-5 hours), thereby preparing a modified polyamide-imide resin.
[0047] The number average molecular weight (Mn) of the modified polyamide-imide resin is preferably in the range of 5,000 to 100,000. More preferably, Mn is in the range of 10,000 to 50,000. If the number average molecular weight (Mn) of the modified polyamide-imide resin is 5,000 or more, the tear strength is excellent and durability can be ensured. If the number average molecular weight (Mn) of the modified polyamide-imide resin is 100,000 or less, the solution viscosity is suppressed to a low level and the processability is excellent. The number average molecular weight (Mn) can be measured by gel permeation chromatography (GPC).
[0048] Polyalkyleneimine is a resin having a polyalkyleneimine skeleton, and is obtained by polymerizing one or more alkyleneimines (e.g., ethyleneimine, propyleneimine) by a common method. The polyalkyleneimine may be a linear polyalkyleneimine composed of a linear polyalkyleneimine chain, or a branched polyalkyleneimine having a branched polyalkyleneimine chain.
[0049] The carbon number of the alkylene group of the polyalkylene imine is preferably 2 to 4. More preferably, it is 2 to 3. Specific examples of the polyalkylene imine include polyethylene imine, polypropylene imine, polybutylene imine, and the like.
[0050] The number average molecular weight of the polyalkyleneimine is preferably 300 to 30000, and more preferably 600 to 10000. The number average molecular weight of the polyalkyleneimine is measured by GPC (gel permeation chromatography) using pullulan as a standard substance.
[0051] Polyoxyethylene alkyl ether is a compound represented by the following general formula (1).
[0052] R-(O-CH2-CH2)n-OH···(1) In formula (1), R is a linear or branched alkyl group, and n is the number of repeating units. The number of carbon atoms in R is preferably 8 or more and 16 or less. More preferably, it is 10 or more and 14 or less. n is preferably 5 or more and 20 or less. More preferably, it is 7 or more and 15 or less.
[0053] The base layer 12 contains polyalkylene imine and polyoxyethylene alkyl ether relative to the modified polyamide-imide resin, so that the friction coefficient can be maintained and the demoulding property can be improved. By using polyalkylene imine and polyoxyethylene alkyl ether relative to the modified polyamide-imide resin, the above effect becomes sufficient. In the case of containing only polyalkylene imine or polyoxyethylene alkyl ether, the above effect is insufficient. Polyalkylene imine and polyoxyethylene alkyl ether have excellent compatibility with the modified polyamide-imide resin, so there are few hidden dangers of reducing physical properties. In addition, there are few hidden dangers of reducing the friction coefficient due to seepage.
[0054] The polyalkylene imine is preferably 0.2 to 20 parts by mass, and the polyoxyethylene alkyl ether is preferably 0.1 to 5 parts by mass, relative to 100 parts by mass of the modified polyamide-imide resin. This can achieve both the effect of maintaining the friction coefficient and the effect of improving the releasability.
[0055] In addition, from the viewpoint of improving mold release, the content of the polyalkylene imide is preferably 0.2 parts by mass or more relative to 100 parts by mass of the modified polyamide-imide resin. More preferably, it is 0.3 parts by mass or more. Furthermore, from the viewpoint of suppressing the reduction of the physical properties of the base layer 12, the content of the polyalkylene imide is preferably 20 parts by mass or less relative to 100 parts by mass of the modified polyamide-imide resin. More preferably, it is 15 parts by mass or less.
[0056] In addition, from the viewpoint of improving mold release, the content of polyoxyethylene alkyl ether is preferably 0.1 parts by mass or more relative to 100 parts by mass of the modified polyamide-imide resin. More preferably, it is 0.2 parts by mass or more. Furthermore, from the viewpoint of suppressing the reduction of the physical properties of the base layer 12, the content of polyoxyethylene alkyl ether is preferably 5 parts by mass or less relative to 100 parts by mass of the modified polyamide-imide resin. More preferably, it is 3 parts by mass or less.
[0057] Furthermore, when the carbon number of the alkylene group of the polyalkylene imine is 2 to 4, the effect of improving the mold release property is excellent. Also, when the carbon number of the alkyl group of the polyoxyethylene alkyl ether is 8 to 16, the effect of improving the mold release property is excellent.
[0058] The base layer 12 may contain other components in addition to the modified polyamide-imide resin, polyalkyleneimine, and polyoxyethylene alkyl ether. Examples of other components include a conductive agent, a filler, and a phosphorus-containing polyester resin.
[0059] Conductive agents include conductive carbon powders such as carbon black and graphite, metal powders such as aluminum powder and stainless steel powder, conductive metal oxides such as conductive zinc oxide, conductive titanium oxide, conductive iron oxide and conductive tin oxide, and ion conductive agents such as quaternary ammonium salts, phosphoric acid esters, sulfonates, aliphatic polyols and aliphatic alcohol sulfates.
[0060] The phosphorus-containing polyester resin functions as a flame retardant. The phosphorus-containing polyester resin preferably has a phosphorus content in the range of 3 to 15% by mass, and more preferably has a phosphorus content in the range of 5 to 10% by mass.
[0061] The base formation material for forming the base layer 12 can be prepared by mixing modified polyamide-imide resin, polyalkylene imine, polyoxyethylene alkyl ether, and other components added as required. In order to apply easily, the base formation material can also be diluted with an organic solvent. As organic solvent, DMF, DMAC, toluene, acetone, NMP, etc. can be listed. The mixing of the base formation material can be carried out using a stirring blade. After mixing, preferably use a ring mill, a ball mill, a sand mill, etc. to disperse them.
[0062] The surface layer 14 can be formed using a surface layer forming material. As the main component of the surface layer forming material, silicone resin, fluorine resin, polyurethane resin, acrylic resin, polyamide resin, etc. can be listed. They can be used alone as the main component of the surface layer forming material, or two or more can be used in combination. Considering the workability, the main component of the surface layer forming material is preferably a liquid or solvent-soluble type. In addition, in order to improve the prevention of dirt, coating strength or tightness, etc., modified resins are preferred. As such modified resins, modified acrylic resins can be listed. As modified acrylic resins, silicone-modified acrylic resins can be listed. As silicone-modified acrylic resins, silicone-grafted acrylic resins can be listed. As silicone-grafted acrylic resins, "SYMAC US-350" manufactured by Toa Synthetics can be listed.
[0063] As the main component, a resin crosslinking agent such as isocyanate resin, amino resin, phenol resin, xylene resin, etc. may be used. In addition, an ultraviolet curing material may be used.
[0064] The surface layer forming material can be prepared by being diluted to organic solvents such as DMF, toluene, acetone and utilizing stirring blades to mix. In addition, in order to form each layer with high accuracy, the organic solvent used for the formation material of adjacent layers preferably uses different kinds from each other. That is, the organic solvent used for the surface layer forming material and the organic solvent used for the base layer forming material preferably use different kinds from each other.
[0065] The base layer 12 of the endless belt 10 can be formed by spraying a base layer forming material on the surface of a mold (cylindrical substrate) and drying it at 150-300° C. for 3-6 hours. The surface layer 14 of the endless belt 10 can be formed by applying a surface layer forming material to the surface of the base layer 12 on the mold by an immersion method and drying it. Thereafter, by blowing air between the base layer 12 and the cylindrical substrate and extracting the cylindrical substrate, the endless belt 10 having a double-layer structure in which the surface layer 14 is formed on the surface of the base layer 12 can be produced.
[0066] In addition, the base layer 12 may be formed by extrusion molding, inflation molding, blow molding, dipping, centrifugal molding, etc. The surface layer 14 may be formed by spraying similarly to the base layer 12 .
[0067] The thickness of the base layer 12 is preferably in the range of 30 to 300 μm, more preferably in the range of 50 to 200 μm. The thickness of the surface layer 14 is preferably in the range of 0.1 to 10 μm, more preferably in the range of 0.5 to 5 μm. The inner circumference of the endless belt 10 is preferably 90 to 1500 mm, and the width is preferably about 100 to 500 mm.
[0068] In the endless belt 10 of the above structure, the base layer 12 is formed by using a modified polyamide-imide resin obtained by copolymerizing the above-mentioned (A) to (C), and contains polyalkylene imide and polyoxyethylene alkyl ether. By incorporating a polydimethylsiloxane structure into the modified polyamide-imide resin by (C), the bending resistance of the endless belt 10 is improved and the friction coefficient can be reduced. In addition, by using polyalkylene imide and polyoxyethylene alkyl ether together with the modified polyamide-imide resin, the friction coefficient can be maintained and the demolding property can be improved.
[0069] The endless belt involved in the present invention can be as follows Figure 1 The substrate shown in the figure has a base layer 12 and a surface layer 14, or it may be composed of only the base layer 12 without the surface layer 14. In addition, there may be other layers between the base layer 12 and the surface layer 14. As other layers, layers composed of resins, layers composed of rubbers, etc. can be listed. They can be one layer or more than two layers. As resins, fluorine-based resins such as polyvinylidene fluoride (PVDF), tetrafluoroethylene-perfluoroalkyl vinyl ether copolymer (PFA), ethylene-tetrafluoroethylene copolymer (ETFE), polyethylene resins, polystyrene resins, acrylic resins, polycarbonate (PC) resins, polyamide resins, EVA (ethylene-vinyl acetate copolymer) resins, EEA (ethylene-ethyl acrylate copolymer) resins, etc. As rubbers, chlorinated polyethylene rubber (CPE), chloroprene rubber (CR), etc. can be listed.
[0070] The endless belt involved in the present invention is preferably used for transferring colorant images, transferring paper, and using as a photosensitive substrate in electronic photographic equipment that adopts electronic photographic technology, such as full-color LBP and full-color PPC, but is not limited to this. For example, it can also be used as a transfer belt of a non-full-color monochrome electronic photographic copier.
[0071] [Example] Hereinafter, the present invention will be described in detail by way of Examples and Comparative Examples. However, the present invention is not limited to the following Examples.
[0072] (Example 1) <Preparation of base layer forming material> 22 parts by mass of MDI, 29 parts by mass of TODI, 38 parts by mass of trimellitic anhydride, 10 parts by mass of silicone polymer (C), and 280 parts by mass of NMP solvent were added to a reaction container equipped with a stirrer, a nitrogen inlet pipe, a thermometer, and a cooling pipe, and the temperature was raised to 130° C. over 1 hour while stirring under a nitrogen flow. After the reaction was maintained at 130° C. for about 5 hours, the reaction was stopped to prepare a PAI-NMP solution (solid content concentration: 29% by mass). 0.2 parts by mass of polyalkylene imine, 0.1 parts by mass of polyoxyethylene alkyl ether, and 5 parts by mass of conductive carbon were added to the prepared PAI-NMP solution, mixed with a stirring blade, and dispersed using a ball mill to prepare a base layer forming material.
[0073] <Manufacturing of Endless Belt> A mold (cylindrical substrate) was prepared, a base layer was formed on the surface of the mold by spraying a base layer forming material, and a heat treatment was performed at 250° C. for 2 hours. Next, air was blown between the base layer and the cylindrical substrate, and the cylindrical substrate was pulled out to produce an endless belt with a single-layer structure having a thickness of 80 μm.
[0074] (Example 2 to Example 10) When preparing the base layer forming material, an endless belt was produced in the same manner as in Example 1 except that the mixing ratio described in the table was used.
[0075] (Comparative Example 1 to Comparative Example 3) When preparing the base layer forming material, an endless belt was produced in the same manner as in Example 1 except that neither the polyalkylene imine nor the polyoxyethylene alkyl ether was blended and the blending ratio described in the table was used.
[0076] (Comparative Example 4 to Comparative Example 5) When preparing the base layer forming material, an endless belt was produced in the same manner as in Example 1 except that zinc stearate was used instead of polyalkylene imine and polyoxyethylene alkyl ether and the mixing ratios described in the table were used.
[0077] (Comparative Example 6) An endless belt was produced in the same manner as in Example 1 except that the silicone polymer was not blended and the blending ratio described in the table was used when preparing the PAI-NMP solution.
[0078] The materials used are described below.
[0079] ·MDI: "MILLIONATE MT" manufactured by Nippon Polyurethane, Mn: 250.26 TODI: "TODI / R203" manufactured by Japan Soda, Mn: 264.29 ·Trimellitic anhydride: Aromatic polycarboxylic anhydride (B1), Mn: 192.12 · Silicone polymer (C): a single-terminal bifunctional silicone polymer having two hydroxyl groups at one terminal: "X-22-176DX" manufactured by Shin-Etsu Chemical Co., Ltd., acid value: 30 mgKOH / g, Mn: 3740 Polyalkyleneimine (polyethyleneimine): "EPOMIN SP-200" manufactured by Japan Catalyst, alkylene carbon number is 2, Mn=10000 Polyoxyethylene alkyl ether: "EMALEX707" manufactured by Japan EMULSION, alkyl carbon number is 12, Mn=495 Zinc stearate: "Zinc stearate NZ-F" manufactured by Nitto Kasei Industries · Conductive carbon: "Ketjen Black EC300J" manufactured by LION SPECIALTY CHEMICALS Using the produced endless belt, various properties were evaluated based on the following criteria.
[0080] (Mold release) After blowing air between the base layer and the cylindrical base, the case where the cylindrical base can be easily pulled out without the need for air is evaluated as good demolding property "○", the case where demolding is possible but air blowing is usually required for demolding is evaluated as "△", and the case where it cannot be pulled out or the base layer is damaged is evaluated as poor "×".
[0081] (Static friction coefficient) The static friction coefficient of each endless belt was measured using a static friction tester μs ("Type 94i" manufactured by HEIDON). The case where the static friction coefficient was 0.04 or more and 0.4 or less was evaluated as "○", and the other cases were evaluated as "×".
[0082] (Bending resistance) According to JIS P8115, the MIT number of each endless belt was measured under a load of 9.8 N using a Folding Endurance tester MIT-D (manufactured by Toyo Seiki Co., Ltd.). The MIT number is an indicator for evaluating the bending resistance, and the greater the MIT number, the better the bending resistance. The case where the MIT number is 1000 times or more is evaluated as "○", and the case where it is less than 1000 times is evaluated as "×".
[0083]
[0084]
[0085] In Comparative Examples 1 to 3, in the base layer forming material, polyalkylene imide or polyoxyethylene alkyl ether was not added to the modified polyamide-imide resin, and the demoulding property was poor. In Comparative Examples 4 to 5, in the base layer forming material, polyalkylene imide or polyoxyethylene alkyl ether was not added to the modified polyamide-imide resin, but zinc stearate was added instead. In Comparative Examples 4 to 5, the friction coefficient was greatly reduced, and the friction coefficient was not maintained within the preferred range. In addition, the MIT number was very small, and the bending resistance was also poor. It is speculated that this is because the modified polyamide-imide resin has poor compatibility with zinc stearate, which results in a reduction in the friction coefficient caused by the oozing of zinc stearate, and in addition, the bending resistance is reduced due to the reduction in physical properties. In Comparative Example 6, when preparing the PAI-NMP solution, the silicone polymer was not added, and the friction coefficient became too large. In addition, the demoulding property is also poor. In addition, the rigidity is too high and the bending property is poor, and the bending resistance is also poor.
[0086] On the other hand, in the examples, the modified polyamide-imide resin was blended with polyalkylene imine and polyoxyethylene alkyl ether, and thus had excellent mold release properties, and the friction coefficient was also within the preferred range, and the bending resistance was also excellent.
[0087] It is understood from the Examples and Comparative Examples that the use of polyalkylene imine and polyoxyethylene alkyl ether together with the modified polyamide-imide resin can provide excellent mold releasability while maintaining the friction coefficient.
[0088] From the comparison between the examples, it can be seen that by increasing the amount of the silicone polymer, the bending resistance is improved (Example 1 to Example 6). It can also be seen that by reducing the amount of polyalkylene imine and polyoxyethylene alkyl ether, the demoulding property is reduced and the friction coefficient is increased (Example 1, Example 7). It can also be seen that by increasing the amount of polyalkylene imine and polyoxyethylene alkyl ether, the friction coefficient is reduced (Example 1, Example 8 to Example 10). Moreover, if the polyalkylene imine is 0.2 mass parts or more and 20 mass parts or less, and the polyoxyethylene alkyl ether is 0.1 mass parts or more and 5 mass parts or less relative to 100 mass parts of the modified polyamide-imide resin, the effect of maintaining the friction coefficient and the effect of improving the demoulding property can be highly achieved at the same time (Example 1 to Example 6).
[0089] As mentioned above, although embodiment of this invention is described in detail, this invention is not limited to the said embodiment, Various changes can be made within the range which does not deviate from the summary of this invention.
Claims
1. An endless belt for an electrophotographic device, which is driven in a circumferential direction in a state where the surface is in contact with or close to a photoreceptor, wherein: The base layer of the endless belt for electrophotographic equipment is formed by using a modified polyamide-imide resin obtained by copolymerizing the following (A) to (C), and contains polyalkylene imine and polyoxyethylene alkyl ether. (A) aromatic isocyanate compounds, (B) anhydrides of aromatic polycarboxylic acids, (C) An organic silicon polymer having a polydimethylsiloxane structure in a molecule and having a reactive group with respect to the isocyanate group of (A) at one or both ends.
2. The endless belt for an electrophotographic apparatus according to claim 1, wherein The polyalkylene imine is in an amount of 0.2 parts by mass or more and 20 parts by mass or less, and the polyoxyethylene alkyl ether is in an amount of 0.1 parts by mass or more and 5 parts by mass or less, based on 100 parts by mass of the modified polyamide-imide resin.
3. The endless belt for an electrophotographic apparatus according to claim 1 or 2, wherein: The organosilicon polymer (C) has a total of two reactive groups of at least one of a hydroxyl group and a carboxyl group at one terminal.
4. The endless belt for an electrophotographic apparatus according to claim 1 or 2, wherein: The blending ratio of the silicone polymer (C) is 1% by mass or more and 20% by mass or less of the total amount of the (A) to (C).
5. The endless belt for an electrophotographic apparatus according to claim 1 or 2, wherein: The alkylene group of the polyalkylene imine has 2 or more and 4 or less carbon atoms.
6. The endless belt for an electrophotographic apparatus according to claim 1 or 2, wherein: The alkyl group of the polyoxyethylene alkyl ether has 8 or more and 16 or less carbon atoms.
7. The endless belt for an electrophotographic apparatus according to claim 1, wherein: The polyalkylene imine is in an amount of 0.2 parts by mass or more and 20 parts by mass or less, and the polyoxyethylene alkyl ether is in an amount of 0.1 parts by mass or more and 5 parts by mass or less, relative to 100 parts by mass of the modified polyamide-imide resin. The organosilicon polymer (C) has a total of two reactive groups of at least one of a hydroxyl group and a carboxyl group at one end. The blending ratio of the silicone polymer (C) is 1% by mass or more and 20% by mass or less of the total amount of the (A) to (C). The carbon number of the alkylene group of the polyalkylene imine is 2 or more and 4 or less, The alkyl group of the polyoxyethylene alkyl ether has 8 or more and 16 or less carbon atoms.
Citation Information
Patent Citations
Endless belt for electrophotographic equipment
JP2005281670A